Development of Interactive Video-Based Learning Media for Physics Material for Students of SMPN 5 Pinrang - Nurnaifah, Ihfa Indira (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
This study developed an interactive video-based learning medium for teaching phase changes in matter to seventh-grade students. The medium, designed using the ADDIE model, was validated as highly suitable, practical, and effective. Expert reviews confirmed its alignment with educational standards, while teacher and student feedback highlighted its engaging and user-friendly features. Significant improvements in students' post-test scores, from 58% to 83%, demonstrated its effectiveness in enhancing understanding and motivation. The interactive video also fostered independent learning and critical thinking, addressing challenges in traditional science education. Despite its success, minor technical issues and additional interactivity needs were identified for future refinement. Overall, the medium offers a practical and innovative solution to improve science education outcomes